The Role Of Multinational Enterprises In Achieving The Sustainable Development Goals (Eurasian Journal of Research, Development and Innovation, 2024)
The 17 Sustainable Development Goals (SDGs) adopted by the United Nations in 2015 present a comprehensive framework for addressing global challenges and promoting a more sustainable and equitable future. Multinational enterprises (MNEs) play a crucial role in achieving these ambitious goals, leveraging their global reach, technological prowess, and financial resources to drive progress. This article examines how MNEs can engage with the SDGs, highlighting both the opportunities and the challenges they face